Differential expression of the ToxR regulon in classical and E1 Tor biotypes of Vibrio cholerae is due to biotype-specific control over toxT expression. - DiRita, V J (1996)
The two major disease-causing biotypes of Vibrio cholerae, classical and El Tor, exhibit differences in their epidemic nature. Their behavior in the laboratory also differs in that El Tor strains produce two major virulence factors, cholera toxin (CT) and the toxin coregulated pilus (TCP), only under very restricted growth conditions, whereas classical strains do so in standard laboratory medium. Expression of toxin and TCP is controlled by two activator proteins, ToxR and ToxT, that operate in cascade fashion with ToxR controlling the synthesis of ToxT. Both biotypes express equivalent levels of ToxR, but only classical strains appear to express ToxT when grown in standard medium. In this report we show that restrictive expression of CT and TCP can be overcome in El Tor strains by expressing ToxT independently of ToxR. An El Tor strain lacking functional ToxT does not express CT or TCP, ruling out existence of a cryptic pathway for virulence regulation in this biotype. These results may have implications for understanding the evolution of El Tor strains toward reduced virulence with respect to classical strains.